2017
DOI: 10.3389/fphys.2017.00662
|View full text |Cite
|
Sign up to set email alerts
|

Larval Mid-Gut Responses to Sub-Lethal Dose of Cry Toxin in Lepidopteran Pest Achaea janata

Abstract: The lack of homogeneity in field application of Bacillus thuringiensis formulation often results in ingestion of sub-lethal doses of the biopesticide by a fraction of pest population and there by promotes the toxin tolerance and resistance in long term. Gut regeneration seems to be one of the possible mechanism by which this is accomplished. However, the existing information is primarily derived from in vitro studies using mid-gut cell cultures. Present study illustrates cellular and molecular changes in mid-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Whereas prolonged exposure to sublethal doses of the toxin inhibits growth, development, and reproduction of larvae, imposing a fitness cost, it might also promote tolerance and resistance of insects to toxins. An earlier report indicated that sublethal doses of toxin had deleterious effects on growth and recovery of Achaea janata ; however, the insects exhibited epithelial cell proliferation in midgut tissue that coincided with elevated arylphorin expression (Chauhan et al, ), similar to the results reported by Castagnola et al (), in H. virescens . These findings identified α‐arylphorin as a protein with a putative role in response to Cry1Ac intoxication.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Whereas prolonged exposure to sublethal doses of the toxin inhibits growth, development, and reproduction of larvae, imposing a fitness cost, it might also promote tolerance and resistance of insects to toxins. An earlier report indicated that sublethal doses of toxin had deleterious effects on growth and recovery of Achaea janata ; however, the insects exhibited epithelial cell proliferation in midgut tissue that coincided with elevated arylphorin expression (Chauhan et al, ), similar to the results reported by Castagnola et al (), in H. virescens . These findings identified α‐arylphorin as a protein with a putative role in response to Cry1Ac intoxication.…”
Section: Introductionsupporting
confidence: 78%
“…In the P. xylostella midgut transcriptome, 2,925 and 2,967 unigenes were differently expressed between two resistant strains compared to susceptible strains, respectively (Lei et al, ). The DEGs were primarily associated with Bt receptors (e.g., ABC transporter, APN, ALP, and CAD), digestive function (α‐amylase, lipase, protease, and carboxypeptidase), immune response (HSC70 and IL22), detoxication enzymes (P450, GST, and CarE), developmental genes (arylphorin), and a variety of binding proteins including cellular retinoic acid‐binding protein (lipid‐binding), insulin‐related peptide‐binding protein (protein‐binding), and ovary C/EBPg transcription factor (nucleic acid‐binding; Sparks, Blackburn, Kuhar, & Gundersen‐Rindal, ; Yang et al, ; Jurat‐Fuentes, Karumbaiah, & Jakka, ; Ocelotl et al, ; Shiho et al, ; Tristan, Sisi & John, , Yao et al, ; Castagnola et al, ; Chauhan et al, ). In this study, the common DEGs were also primarily associated with digestion function, with enriched GO terms including monocarboxylic acid metabolic process, pyruvate metabolic process, lipid biosynthetic process, and serine‐type endopeptidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the larval midgut transcriptome was sequenced and analyzed by Novogene, and 151,090 high-quality unigenes were obtained, including 1660, 1175, and 562 DEGs between the three larvae treatments with Cry1Ac toxin and the control, respectively. In the P. xylostella midgut transcriptome, 2925 and 2967 unigenes were differently expressed between two resistant strains compared to susceptible strains, Chauhan et al, 2017). In this study, the common DEGs were also primarily associated with digestion function, with enriched GO terms including monocarboxylic acid metabolic process, pyruvate metabolic process, lipid biosynthetic process, and serine-type endopeptidase activity.…”
Section: Genes Of Interest and Bt-related Genes In The Transcriptome mentioning
confidence: 53%
“…These genes were significantly enriched in nine functional categories, four of which, Glutathione metabolism, Drug metabolism-cytochrome P450, Metabolism of xenobiotics by cytochrome P450, and Chemical carcinogenesis, are related to detoxification and immunity (Table 10). (Chauhan VK, et al 2017). In the present study, a 7.5 µg/mL dosage of Bt Cry1Ac toxin solution with sodium carbonate represented a sub-lethal dose, much lower than for other species, suggesting that the C.…”
Section: Genes Of Interest and Bt-related Genes In The Transcriptome mentioning
confidence: 99%
“…However, in CF1 cells the Cry toxicity was not associated with PKA pathway (Portugal et al, 2017). Recent studies revealed that Cry toxin induces necrotic cell death in B.mori ABCC2 transfected Sf9 cells (Endo et al, 2017) as well as in larval midgut of A. janta (Chauhan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%